Hartmann–Sprenger effect and its application on aircraft - V. I. KuznetsovV. I. Kuznetsov; A. Yu. Shander (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The question of the effect of viscosity on the occurrence of a stagnation temperature in a dead-end cavity above the deceleration temperature of the incident gas flow the so-called Hartmann–Sprenger effect is considered. It is shown that the Hartmann–Sprenger effect can be used to create the design of the anti-icing system of the aircraft